STRESS AND STRESS COPING STRATEGIES AMONG STUDENTS WITH DISABILITIES AT COLLEGE OF TECHNOLOGY EDUCATION - Gyasi, Ficus; Asiamah Yeboah, Kofi (IJRDO- Journal of Educational Research, 2020)
AbstractStudents with disability accessing tertiary education worldwide continue to experience various degrees of stress. To understand this phenomenon from the Ghanaian perspective, we have undertaken this study to investigate stress and stress coping strategies among students with disability at College of Technology Education, Kumasi-Ghana. The study adopted a descriptive phenomenology on eighteen (18) participants. The data was collected using semi-structured interview guide and analyzed using thematic technique. The results identified three sources of stress, namely: fear of examination, discrimination and incompatible infrastructure. The coping strategies adopted by the students with disabilities were self-determination, dependence on God, and support from relatives and peers. This paper makes two valuable recommendations that the university authorities institute policies that would ensure a disability friendly campus and to make guidance and counselling services accessible to students with disabilities to support them to address their counselling needs.